FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA BAGIAN PRODUKSI NYLON, POLYESTER, DAN RESIN DI PT X KOTA TANGERANG - Putri Hardyanti (2020)
Personal protective equipment (PPE) is used to protect the safety of workers. The behavior of using PPE that is not good plays the biggest role in the occurrence of work accidents by 80%-85%. This study aims to identify individual characteristics, predisposing, enabling, and reinforcing factors that may have an impact on the behavior of nylon, polyester, and resin production workers at PT. X Tangerang City in using PPE. This research is a cross-sectional study. A sample of 82 workers was collected using a purposive sampling technique. The Chi-square test was used to analyze the data, and the questionnaire as a research method was followed by the logistic regression test. According to the findings, 80.5% of workers showed good behavior in using PPE, while 19.5% did not. The results of statistical testing indicate that a number of factors are significantly related to the behavior of using PPE, including education level; P = 0.048 (OR: 4,333 CI: 1,129-16,631), knowledge; P = 0.001 (OR: 38,309 CI: 4,239-358,807), OHS training; P = 0.023 (OR: 4.077 CI: 1.288-12.908), and the perception of the policy on the use of PPE; P = 0.026 (OR: 4.350 CI: 1.242-15.233). Factors that influence the behavior of using PPE are education level (OR: 4,795 CI: 1,000-22,996), knowledge (OR: 38,309 CI: 3,228-44,647), and OSH training (OR: 6,218 CI: 1,420-27,226). The use of PPE by nylon, polyester, and resin production workers at PT X Tangerang City is thus determined by knowledge, which is the most important component. The probability of a worker using PPE correctly is 38 times higher if they have good knowledge.